2011
DOI: 10.5507/bp.2011.024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Psychological Intervention on Perceived Pain in Children Undergoing Venipuncture

Abstract: Aims. The main objective of the study was to determine the effect of structured psychological intervention on the level of perceived pain in children undergoing venipuncture. A second goal was to investigate how pain behavior during venipuncture is affected by age, sex, previous number of venipunctures, the presence of parents during the procedure and reason for the venipuncture.Methods. Children with indications for venipuncture aged 5-10 years, were randomly divided into a control group and an intervention g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
3
15
1
2
Order By: Relevance
“…A study conducted by Lucie Sikorova, Petra Hrazdilova [10] also supports the findings of present study who revealed that a greater level of pain was in children where the parents were present. The psychological intervention carried out by a nurse proved to lower pain levels from venipuncture as measured by the CHEOPS scale and evaluated using the self-report scale.…”
Section: Discussionsupporting
confidence: 79%
“…A study conducted by Lucie Sikorova, Petra Hrazdilova [10] also supports the findings of present study who revealed that a greater level of pain was in children where the parents were present. The psychological intervention carried out by a nurse proved to lower pain levels from venipuncture as measured by the CHEOPS scale and evaluated using the self-report scale.…”
Section: Discussionsupporting
confidence: 79%
“…18 Our study confirms this finding. In addition, prior authors have reported sex differences in pain behavior.…”
Section: Discussionsupporting
confidence: 95%
“…Previous authors have demonstrated that distraction techniques and a reward, such as bubbles, music, or toys, lower pain behavior in children during minor procedures such as venipuncture or the placement of intravenous lines. [14][15][16][17][18][19] In the present study, we utilized stickers and lollipops as distraction and reward techniques for each child. Distraction techniques are simple, practical, effective, and inexpensive pain management strategies for children.…”
Section: Discussionmentioning
confidence: 99%
“…Pain perception severity regarding inserting a needle into the vein is related to patient's age and his/her former pain experiences . Investigators put forward that affective factors such as anxiety and fear have a substantial impact on the perception of venipuncture pain . Combined with affective factors, cognitive characteristics, which are depicted in PCS, may play a significant role in the perception of venipuncture pain.…”
Section: Introductionmentioning
confidence: 99%